Scan rate Dependent Factor for Antioxidant Activity of Gold Nanofilms Synthesized via Cyclic Voltammetry Technique - Babay Asih Suliasih; Dwi Giwang Kurniawan; Annisa Auliya; Marissa Angelina (Pusat Inovasi Sains, 2023)
Gold nanoparticles (AuNPs) were found to act as antioxidants owing to their inert, high stability, biocompatibility, and non-cytotoxic. The present investigation involved the synthesis of gold nanoparticles through the electrodeposition technique on a substrate comprising Fluorine-doped Tin Oxide (FTO). By manipulating the scan rate parameter, an effective approach can be employed to facilitate precise management of particle morphology and size. The obtained shape of AuNPs were spherical and irregular. In this study, it was observed that gold nanoparticles elicited potent inhibition, particularly at a scan rate of 150 mV/s, with a markedly high inhibition value of 41.27%. The outcome was further supported by an augmented particle distribution density per unit area, which measured as 149,635,036.5/mm².